MILLIY DÁSTÚRLER, ÚRP-ÁDETLERDIŃ TIYKARǴÍ FUNKCIYALARÍ HÁM RUWHÍY TÁRBIYADAǴÍ ÁHMIYETI - Utepbergenova, S.M. (ILIM hám JÁMIYET, 2023)
The article touches on the main functions that the author performs in the national programs and customs of your team. Therefore, in his service, he revealed their importance in spiritual education, mainly in the upbringing of children.